Continuous Subcutaneous Insulin Infusion in Children: A Pilot Study Validating a Protocol to Avoid Hypoglycemia at Initiation - Manousaki, Despoina; Deladoëy, Johnny; Geoffroy, Louis; Olivier, Patricia (Frontiers in Endocrinology, 2017)
Background: The occurrence of hypoglycemia and hyperglycemia during the first days after transition to continuous subcutaneous insulin infusion (CSII) in patients with type 1 diabetes has not been systematically studied in children. The aim of this prospective study was to demonstrate that the protocol applied in our diabetes clinic is safe at CSII initiation in children. Methods: We assessed 22 pediatric patients with type 1 diabetes, using continuous glucose monitoring before and after CSII initiation (± 3 days). Results: After CSII initiation, there was no difference in the rates of hypoglycemic events expressed as relative rates per person-reading (RR=0.85, p=0.52, 95% CI 0.52-1.39), as well as in the number of prolonged hypoglycemic events (>1 hour) per day (RR=1.12, p=0.56, 95% CI 0.75-1.68). We observed only a trend towards prolonged episodes of hyperglycemia after pump initiation (RR=1.52, p=0.06, 95% CI 0.97-2.35). Conclusions: Our study is the first to assess, through continuous glucose monitoring and in a prospective way, the impact of a CSII initiation protocol on glycemic values. Our protocol provides a safe model to avoid hypoglycemia at CSII initiation in children.